Standing alone with prosodic help* - Frazier, Lyn (2013)
Two partially independent issues are addressed in two auditory rating studies: under what circumstances is a sub-string of a sentence identified as a stand-alone sentence, and under what circumstances do globally ill-formed but ‘locally coherent’ analyses (Tabor, Galantucci, & Richardson., 2004) emerge? A new type of locally coherent structure is established in Experiment 1, where a that-less complement clause is at least temporarily analyzed as a stand-alone sentence when it corresponds to a prosodic phrase. In Experiment 2, reduced relative clause structures like those in Tabor et al. were investigated. As in Experiment 1, the root sentence (mis-)analyses emerged most frequently when the locally coherent clause corresponded to a prosodic phrase. However, a substantial number of locally coherent analyses emerged even without prosodic help, especially in examples with for-datives (which do not grammatically permit a reduced relative clause structure for some speakers). Overall, the results suggest that prosodic grouping of constituents encourages analysis of a sub-string as a root sentence, and raise the question of whether all local coherence structures involve analysis of an utterance-final sub-string as a root sentence.